Antifungal Activity of the Essential Oils of Two Verbenaceae: Lantana achyranthifolia and Lippia graveolens of Zapotitlán de las Salinas, Puebla (México) - Tzasna Hernández (Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas, 2008)
The present work documents the antifungal activity of the essentials oils of Lantana achyranthifolia Desf. and Lippia graveolens H.B.K. Theessential oils of aerial parts of L. achyranthifolia and L. graveolens were obtained by steam distillation and examined by GC and GC-MS.Antifungal activity of the essentials oils was evaluated towards five fungal strains by the disk-diffusion method. The estimation of the Medium Inhibitory Concentration (IC50) was carried out by the inhibition of fungal growth method. The oils presented antifungal activityagainst five fungal strains; the essential oil of L. graveolens presented higher antifungal activity (IC50= 1090 μg/mL) than L. achyranthifolia (IC50= 100180 μg/mL). The present study validates the use in the folk medicine of L. achyranthifolia and L. graveolens for treating dermatological diseases and could be an option for the biological control of phytopathogen strains.